British literature in transition, 1920-1940 : futility and anarchy - Ferrall, Charles; McNeill, Dougal, 1981- (Cambridge : Cambridge University Press, 2018)
Literature from the'political' 1930s has often been read in contrast to the'aesthetic' 1920s. This collection suggests a different approach. Drawing on recent work expanding our sense of the political and aesthetic energies of interwar modernisms, these chapters track transitions in British literature. The strains of national break-up, class dissension and political instability provoked a new literary order, and reading across the two decades between the wars exposes the continuing pressure of these transitions. Instead of following familiar markers - 1922, the Crash, the Spanish Civil War - or isolating particular themes from literary study, this collection takes key problems and dilemmas from literature'in transition' and reads them across familiar and unfamiliar cultural works and productions, in their rich and contradictory context of publication. Themes such as gender, sexuality, nation and class are thus present throughout these essays. Major writers such as Woolf are read alongside forgotten and marginalised voices.
Machine generated contents note: Introduction Charles Ferrall and Dougal McNeill; Part 1. After the War; 1. Out of Mrs Colefax's Drawing-Room: Poets and Poetry between the Wars Harry Ricketts; 2. Perverting the Postwar: Sexuality and State Violence in Women's Literature Layne Parish Craig; 3. Journeys without Maps: Literature and Spiritual Experience Lara Vetter; Part 2. Literature after Human Nature Changed; 4. Writing the Vote: Suffrage, Gender, and Politics Sowon S Park and Kathryn Laing; 5. Literature and Human Rights Rachel Potter; 6. Psychoanalysis and Modernism John Farrell; Part 3. Immense Panoramas of Futility and Anarchy: Writing and Politics; 7. History: the Past in Transition Gabrielle McIntire; 8. Women's Work? Domestic Labour and Proletarian Fiction Charles Ferrall; 9. Ordinary Places, Intermodern Genres: Documentary, Travel, and Literature Kristin Bluemel; 10. Bloomsbury Conversations that Didn't Happen: Indian Writing between British Modernism and Anti-Colonialism Snehal Shingavi and Charlotte Nunes; Part 4. The First Break-Up of Britain; 11. Between Holyhead and Kingstown: Anglo-Irish Perspectives on the character of British fiction Michael G Cronin; 12. Cancer of Empire: The Glasgow Novel between the Wars Liam McIlvanney; 13. Lewis Jones and the Making of Welsh Identity Shintaro Kono; 14. From Optik to Haptik: Celticism, Symbols and Stones in the 1930s Peter Mackay; Part 5. Transitions High and Low; 15. On the Home Front: Designs for Living in British Drama between the Wars Penny Farfan; 16. Middlemen, Middlebrow, Broadbrow Nicola Wilson; 17. Detective Fiction: Resolutions without Solutions J. C. Bernthal; 18. British Literature in Transmission: Writing and Wireless James Purdon.
Title from publisher's bibliographic system (viewed on 11 Dec 2018).
Keywords: English literature -- 20th century -- History and criticism; Literature and society -- Great Britain -- History -- 20th century